TRANSIENT WITH MYOCARDIAL INFARCTION CLINICAL-NEUROLOGICAL CHARACTERISTICS OF ISCHEMIC STROKE DEVELOPMENT (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Transient ischemic attack (TIA) can convey a high imminent risk for the development of a major stroke and is therefore considered to be a medical emergency. Recent evidence indicates that TIA with imaging proof of brain infarction represents an extremely unstable condition with early risk of stroke that is as much as 20 times higher than the risk after TIA without tissue damage. The use of neuroimaging in TIA is therefore critical not only for diagnosis but also for accurate risk-stratification. In this article, we discuss recent advances in diagnostic imaging, categorizations, and risk stratification in TIA.